Mother-tongue influence in the pronunciation contrast of the English /i/and/i/vowel sounds among Malaysian Malay esl speakers - Tan, Li-Lian @ Lillian Tan. (Universiti Malaysia Sarawak, (UNIMAS), 1997)
Language transfer has been a controversial topic that has been the debate of many linguists, language teachers and instructors. This paper investigates the existence of such transfer in Malaysian Malay ESL speakers in the production of the English vowel sounds %i/ and /d. It has been found that the majority of the speakers do not differentiate between the long and short vowel sounds. They do not pronounce the long /i/ vowel sound with accuracy as the sound does not exist in their mother-tongue language (Malay). The main reason for this is the frequent use of their mother-tongue and also the amount of exposure they have to Malay. English is only used occasionally as it does not play a major role in their communication everyday. Several factors are also speculated on in this paper, emphasising individual differences which may cause the problem. Among the recommendations suggested are activities that could be employed in ESL classrooms during English lessons in aid of students who face the similar problem.